2016
DOI: 10.1186/s12936-015-1069-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of G6PD deficiency in two Plasmodium vivax endemic areas in Venezuela: predominance of the African A-202A/376G variant

Abstract: Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency causes acute haemolytic anaemia triggered by oxidative drugs such as primaquine (PQ), used for Plasmodium vivax malaria radical cure. However, in many endemic areas of vivax malaria, patients are treated with PQ without any evaluation of their G6PD status.Methods: G6PD deficiency and its genetic heterogeneity were evaluated in northeastern and southeastern areas from Venezuela, Cajigal (Sucre state) and Sifontes (Bolívar state) municipalities, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
3
8
0
3
Order By: Relevance
“…This difference would be related to the criteria of inclusion of the patients but especially to the method of detection which was rather biochemical. The male prevalence found in this study has been described by many authors including Vizzi et al (2016) in Venezuela, which found a prevalence of 5.5% in men as compared to 4.1% in women (p ˂ 0.007). Similar results were also obtained by Benkerrou et al (2013) with respectively 16% of men versus 10% with women.…”
Section: Discussionsupporting
confidence: 79%
“…This difference would be related to the criteria of inclusion of the patients but especially to the method of detection which was rather biochemical. The male prevalence found in this study has been described by many authors including Vizzi et al (2016) in Venezuela, which found a prevalence of 5.5% in men as compared to 4.1% in women (p ˂ 0.007). Similar results were also obtained by Benkerrou et al (2013) with respectively 16% of men versus 10% with women.…”
Section: Discussionsupporting
confidence: 79%
“…According to the previous epidemiologic studies, the prevalence rate of G6PD deficiency is higher among males than females [11,27,[30][31][32][33][34][35]. In line with these studies, the current study also revealed a higher prevalence rate of G6PD deficiency among males compared to the females.…”
Section: Discussionsupporting
confidence: 80%
“…Also, in malarious regions of the world, the prevalence rate of G6PD deficiency was reported to be 8% on average [25] which is lower than that (12%) in the present study. Nevertheless, the prevalence rate of the current report is lower than that of some parts of the world including Zuniga in Honduran (16.8%) [26] and is higher than that of some other areas such as Venezuela (3.6%) [26,27]. Interestingly, rate of G6PD deficiency among study participants in southeast and north of Iran is considerably higher than that in south and central part of Iran [28,29].…”
Section: Discussionmentioning
confidence: 43%
“…Ahora bien, si la mezcla génica fuera efectiva entre indígenas Piaroas e individuos de las ciudad (que la población indígena este integrada a la mestiza urbana y no aislada o desplazada), es de esperar deficiencia bioquímica de G6PD clase III, la que caracteriza a la población venezolana y que se corresponde con individuos con deficiencia enzimática de leve a moderada, en los cuales la sintomatología hemolítica es desencadenada únicamente por la exposición a sustancias que inducen estrés oxidante 18,39,40 .…”
Section: Discussionunclassified
“…Por tanto, un importante aspecto a considerar en estudios genéticos por el agravamiento de la hemolisis de eritrocitos, y en consecuencia del grado de anemia, es la determinación poblacional de G6PD en el tratamiento del paludismo, respecto a la posibilidad de aumento de la dosis o la prolongación del número de días de tratamiento en los casos de resistencia o recidiva, particularmente porque el descubrimiento de hemólisis en hombres con deficiencia de G6PD como resultado de tratamiento antimalárico con primaquina data de 1950, y especialmente cuando en 2016 se publica una prevalencia de 3,5% de deficiencia de G6PD en zonas venezolanas (Bolívar y Amazonas) endémicas de paludismo, en que se excluye a la población indígena por considerar escaso su flujo génico [11][12][13][14][15][16][17][18] . En este sentido, en Venezuela, de Acquatella desde 1966 19 no encuentra deficiencia de G6PD en indígenas paraujanos (de la Guajira venezolana), pero debido a la inesperadas cifras de sujetos con anemia hemolítica aguda en indígenas yanomamo (de las comunidades de Ocamo y Mavaca del estado Amazonas), poblaciones con amplia exposición a infección por paludismo y alta prevalencia de síndrome de esplenomegalia hiperactiva a Plasmodium spp., se llevan a cabo estudios para indagar la etiología de estos inusuales casos de anemia hemolítica severa, en que se demuestra que la condición hemolítica está asociada a aglutinación mediada por repuesta autoinmune y no a defectos hereditarios de membrana de eritrocitos, hemogloginopatías o deficiencia de G6PD u otras anormalidades enzimáticas asociadas con hemólisis [20][21][22] .…”
Section: Introductionunclassified